Age-related macular degeneration – a complex genetic disease - Antoniak, Katarzyna; Bienias, Wojciech; Nowak, Jerzy (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Age-related macular degeneration (AMD,) is the most common cause of severe visual loss and blindness in the population over 60 years old, especially in the developed world. Two types of AMD are distinguished: the dry (non-exudative or atrophic) and the wet (exudative or neovascular) form. Family and twins studies have shown that the susceptibility for this disease is genetically influenced and the heritability has been estimated to be up to 75%. Until now, many of the candidate-genes associated with AMD have been discovered using studies on genetically engineered and naturally mutated animals, linkage studies, studies of monogenic degenerative retinal diseases and association studies. Recently genes have been described that significantly contribute to the etiopathogenesis of AMD: CFH, PLEKHA1/LOC387715/HTRA1 and C2/BF genes. AMD is considered to be a genetic complex disease in which multiple genes and environmental factors play a role in pathogenesis. Identification of other genes involved in development of AMD will improve our knowledge about new pathways and pathological mechanisms of the disease, as well as avenues for novel more effective treatments. The aim of this article is to survey published data on genetic aspect of AMD, with emphasis of several recently discovered genes described to be particularly important in the pathogenesis of AMD, and /or somehow associated with the occurrence of the disease.